Skeleton man - Bruchac, Joseph, 1942- (New York : HarperCollins, 2001)
After her parents disappear and she is turned over to the care of a strange "great-uncle," Molly must rely on her dreams about an old Mohawk story for her safety and maybe even for her life.
Wilson's Children.
Wilson's Junior High School.
School Library Journal starred.
5.3
5-8
Keywords: Psychopaths -- Fiction; Kidnapping -- Fiction; Mohawk Indians -- Fiction; Indians of North America -- New York (State) -- Fiction; Abnormal psychology -- Fiction; Kidnapping -- Fiction; Mohawk Indians -- Fiction; Native Americans -- New York (State) -- Fiction; Kidnapping -- Fiction; Mohawk Indians -- Fiction; Indigenous people of North America -- Fiction